2010
DOI: 10.1002/med.20211
|View full text |Cite
|
Sign up to set email alerts
|

Telomere/telomerase interplay in virus‐driven and virus‐independent lymphomagenesis: pathogenic and clinical implications

Abstract: Telomerase is a ribonucleoprotein complex critically involved in extending and maintaining telomeres. Unlike the majority of somatic cells, in which hTERT and telomerase activity are generally silent, normal lymphocytes show transient physiological hTERT expression and telomerase activity according to their differentiation/activation status. During lymphomagenesis, induction of persistent telomerase expression and activity may occur before or after telomere shortening, as a consequence of the different mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 123 publications
1
25
1
Order By: Relevance
“…Consistent with the notion that telomerase is involved in more cell processes than mere maintenance of telomere length (38), this study provides evidence that, besides inducing EBV lytic cycle, hTERT inhibition has antiproliferative and proapoptotic effects that may be of therapeutic importance. While hTERT inhibition in EBV-negative Burkitt's lymphoma cells induced accumulation of cells in G 0 -G 1 , as shown in other cell systems (39)(40)(41), infection of EBV-positive Burkitt's lymphoma cells with shTERT3.4 resulted in a marked increase of cells in the S-phase.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with the notion that telomerase is involved in more cell processes than mere maintenance of telomere length (38), this study provides evidence that, besides inducing EBV lytic cycle, hTERT inhibition has antiproliferative and proapoptotic effects that may be of therapeutic importance. While hTERT inhibition in EBV-negative Burkitt's lymphoma cells induced accumulation of cells in G 0 -G 1 , as shown in other cell systems (39)(40)(41), infection of EBV-positive Burkitt's lymphoma cells with shTERT3.4 resulted in a marked increase of cells in the S-phase.…”
Section: Discussionsupporting
confidence: 86%
“…cortisol [27], may compromise telomerase activity, while mitogenic stimulation, e.g. antigen stimulation for B lymphocytes [28], may induce it [29,30]. Thus, we detected the ability of DN B cells to reactivate telomerase by the engagement of both innate and adaptive immune receptors.…”
Section: Introductionmentioning
confidence: 97%
“…TP53 alone may be inefficient in regulating TERT, since many other factors activate or repress TERT at a transcriptional level. 7 Our findings suggest that TP53 plays an important role in TERT regulation in 13q14del CLL, while in CLL with no or other chromosomal aberrations TERT may be regulated by other factors.…”
mentioning
confidence: 60%
“…Telomerase expression, up-regulated in approximately 90% of human cancers, enables continuous and uncontrolled proliferation of the malignant cells driving tumor growth and progression. 7 Catalytic protein with telomere-specific reverse transcriptase activity (TERT) is the rate-limiting component of the telomerase complex, and its expression is correlated with telomerase activity. 8 We and others have shown that levels of TERT and its activity are prognostic markers in CLL.…”
mentioning
confidence: 99%